2019
DOI: 10.1017/s1751731118002173
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of farmed red deer fed a balanced diet: effects of supplementation with copper bolus on different muscles

Abstract: Supplementation with copper (Cu) improves deer antler characteristics, but it could modify meat quality and increase its Cu content to levels potentially harmful for humans. Here, we studied the effects of Cu bolus supplementation by means on quality and composition of sternocephalicus (ST) and rectus abdominis (RA) muscles (n=13 for each one) from yearling male red deer fed with a balanced diet. Each intraruminal bolus, containing 3.4 g of Cu, was administered orally in the treatment group to compare with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Current results are similar to those observed by Hutchison et al . for the longissimus dorsi muscle from fallow deer does fed on pasture or grain and by Serrano et al . for sternocephalicus and rectus abdominis muscles from red deer fed on balanced diets.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Current results are similar to those observed by Hutchison et al . for the longissimus dorsi muscle from fallow deer does fed on pasture or grain and by Serrano et al . for sternocephalicus and rectus abdominis muscles from red deer fed on balanced diets.…”
Section: Discussionsupporting
confidence: 91%
“…who claimed that protein content in deer meat may vary between 20% to as high as 25%, thus confirming that deer meat is a relatively rich source of proteins. Finally, ash content (1.23% as average in the current study) is very similar (approximately 1% to 2%) in all deer species and in all muscles and comparable across most studies . Values for chemical composition obtained in the current study were thus similar to those reported in the literature for meat from farmed fallow deer and from farmed red deer feeding on pastures …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Taking into account that genetic factors influence enzymatic activities and that the meat composition influence the biochemical changes produced during the different stages of dry‐cured meat process (Bermúdez et al ., ), the results obtained in this research will provide us with information about the possibility of using deer meat for the preparation of dry‐cured loin. In this context, venison meat is characterised by low fat and cholesterol contents and high levels of protein, essential amino acids, essential and long‐chain polyunsaturated fatty acids and iron (Lorenzo et al ., ; Maggiolino et al ., ; Serrano et al ., ).…”
Section: Introductionmentioning
confidence: 99%